Standard form Ax + By = C
so
<span>(y - y1) = m(x - x1)
</span>given (5, -7) and m = -1/5
so
y + 7 = -1/5(x - 5)
-5y - 35 = x - 5
x + 5y = -30
answer
d. x + 5y = -30
You can see that the term
appears in both equations. In this cases, we can leverage this peculiarity and subtract the two equations to get rid of the repeated term. So, if we subtract the first equation from the second, we have
![(-4x -6y) - (-10x-6y) = 54-0 \iff 6x = 54 \iff x = 9](https://tex.z-dn.net/?f=%20%28-4x%20-6y%29%20-%20%28-10x-6y%29%20%3D%2054-0%20%5Ciff%206x%20%3D%2054%20%5Ciff%20x%20%3D%209%20)
Now that we know the value of
, we can substitute in any of the equation to deduce the value of
: if we use the first equation, for example, we have
![-10x-6y=0 \iff -10\cdot 9 - 6y = 0 \iff -90-6y=0 \iff 6y = -90 \iff y = -15](https://tex.z-dn.net/?f=%20-10x-6y%3D0%20%5Ciff%20-10%5Ccdot%209%20-%206y%20%3D%200%20%5Ciff%20-90-6y%3D0%20%5Ciff%206y%20%3D%20-90%20%5Ciff%20y%20%3D%20-15%20)
Answer:
1188 grams of water
Step-by-step explanation:
x is the grams of water
so total is 12+x grams
sugar/total is 12/12+x
and 1% ratio is 12/12+x=1/100
so x would be 1188 grams of water.
2464 ÷ 2 = 1232 ;
1232 is half of 2464.